PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. PRATAMA ABADI INDUSTRI SERPONG - Muhamad Rizki; Ibrahim Bali Pamungkas (Journal of Research and Publication Innovation, 2025)
The purpose of this study was to determine the effect of work discipline and work environment on employee performance at PT Pratama Abadi Industri Serpong partially and simultaneously. The method used is Quantitative. The sampling technique used Saturation and obtained a sample of 60 Respondents. Data analysis using Validity test, Reliability Test, Classical Assumption Test, Regression Analysis, Correlation Coefficient, Coefficient of Determination and Hypothesis. The result of this study is that work discipline has a significant effect on employee performance with a coefficient of determination of 29.5% and the hypothesis test obtained tcount> ttable = (4.925> 2.002). The work environment has a significant effect on employee performance with a coefficient of determination of 63.4% and the hypothesis test obtained tcount> ttable = (6,243> 2,002). Work Discipline and Work Environment simultaneously have a significant effect on Employee Performance with the Regression Equation Y = 13, 813 + 0.050X1 + 0.620X2. The coefficient of determination is 40.2% while the remaining 59.8% is caused by other variables. Hypothesis Test obtained Fhitung> Ftabel or (19.195> 3.16).